Observational information on a temperate reef community helps understanding the marine climate and ecosystem shift of the 1980–90s. Issue 1 (15th January 2017) - Gatti, Giulia; Bianchi, Carlo Nike; Montefalcone, Monica; Venturini, Sara; Diviacco, Giovanni; Morri, Carla
Abstract: The dearth of long-time series hampers the measurement of the ecosystem change that followed the global marine climate shift of the 1980–90s. The sessile communities of Portofino Promontory reefs (Ligurian Sea, NW Mediterranean) have been discontinuously studied since the 1950s. Collating information from various sources, three periods of investigations have been distinguished: 1) 1950–70s; 2) 1980–90s; 3) 2000–10s. A cooler phase in time 1 was followed by a rapid warming in time 2, to stabilize at about 0.5 °C higher in time 3. Human pressure grew impressively, especially after the establishment of a MPA in 1999. Multivariate analyses evidenced a major change of community composition in time 2. Some species disappeared or got rarer, many found refuge at depth, and among the newcomers there were recently introduced alien species. This study demonstrated the importance of descriptive historical data to understand magnitude and pattern of change in the long term evolution of marine ecosystems. Highlights: Observational information is often more available than rigorous quantitative data. Descriptive historical data allowed analysing the 1980–90s' marine climate shift. Three periods of investigations: 1) 1950–70s; 2) 1980–90s; 3) 2000–10s. Major changes occurred in time 2, community composition and structure shifted. Some species disappeared/got rarer, others found refuge in depth, new species came.